Lyapunov stability and weak attraction for control systems - Rocha, Victor H. L. [UNESP]; Reis, Ronan A. [UNESP] (Universidad Catolica del Norte - Chile, 2022)
In this paper we deal with Lyapunov stability and weak attraction for control systems. We give characterizations of the stability and asymptotical stability of a compact set by means of its components. We also study the asymptotical stability of the prolongation of a compact weak attractor
Keywords: Asymptotical stability; Connected components; Control systems; Lyapunov stability; Prolongations